2005
DOI: 10.1111/j.1365-2567.2004.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility class II molecules prevent destructive processing of exogenous peptides at the cell surface of macrophages for presentation to CD4 T cells

Abstract: Summary We studied factors affecting major histocompatibility complex class II (MHC‐II)‐restricted presentation of exogenous peptides at the surface of macrophages. We have previously shown that peptide presentation is modulated by surface‐associated proteolytic enzymes, and in this report the role of the binding of MHC‐II molecules in preventing proteolysis of exogenous synthetic peptides was addressed. Two peptides containing CD4 T‐cell epitopes were incubated with fixed macrophages expressing binding and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Antigen processing of whole mycobacteria‐derived antigens for MHC class II presentation on the surface of antigen presenting cells requires phagocytosis, processing, and intracellular vesicular trafficking to allow the formation of peptide‐MHC‐II complexes . Soluble, exogenous synthetic peptides can be directly loaded onto MHC class II molecules present on the surface of antigen‐presenting cells and presented to CD4 + T cells . Head to head comparison of synthetic peptides versus whole‐mycobacteria to recall immune memory in vitro distinguishes between ex vivo assessment of CD4 + T cell frequencies directed against a specific antigen from the capacity of antigen‐presenting cells to uptake bacteria, process and present bacteria‐derived antigens to CD4 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Antigen processing of whole mycobacteria‐derived antigens for MHC class II presentation on the surface of antigen presenting cells requires phagocytosis, processing, and intracellular vesicular trafficking to allow the formation of peptide‐MHC‐II complexes . Soluble, exogenous synthetic peptides can be directly loaded onto MHC class II molecules present on the surface of antigen‐presenting cells and presented to CD4 + T cells . Head to head comparison of synthetic peptides versus whole‐mycobacteria to recall immune memory in vitro distinguishes between ex vivo assessment of CD4 + T cell frequencies directed against a specific antigen from the capacity of antigen‐presenting cells to uptake bacteria, process and present bacteria‐derived antigens to CD4 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the protease activities could be similar in the different mouse strains, but the MHC-II of the BALB/c strain (I-A d ) could have lower average peptide-binding affinity than the MHC-II of the other mouse strains; and therefore, I-A d protects a smaller fraction of epitope molecules from destruction. MHC-II proteins have been shown to protect epitopes from proteolytic destruction (61)(62)(63). Further studies in the genetically defined MHC backgrounds of mice will be necessary to generalize mechanisms of antigen processing and then extend them to heterogeneous systems such as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The results of such studies [5-8, 11,12] have demonstrated an effective processing of bacterial antigens and binding of antigenic fragments to MHC class II molecule for presentation to CD4 T cells. Two epitopes from streptococcal M5 protein (M5 17-31 and M5 308-319) have been studied to investigate the mechanism of Ag processing and presentation using mouse macrophages and T cell hybridomas specific for each epitopes [23][24][25][26][27][28][29]. This approach is the basis for bacterial vaccines development.…”
Section: Introductionmentioning
confidence: 99%